(untitled) (Research, Society and Development, 2021)
The successive changes in Brazilian educational policies have caused aggravating consequences in education. Therefore, this article aims to highlight how the process of elaboration of the Common National Curriculum Base took place through educational documents published since the 1988 Constitution. It is a bibliographic and documentary research, of advanced nature, of exploratory and explanatory nature, and with a qualitative approach, where several documents were studied from the Constitution of 1988 to the last version of the BNCC, and scientific articles. For a better understanding of the research, a chronological order was constructed among the main educational documents. In view of all the work, it is concluded that the implementation process of the BNCC is something that has been planned during the years by only one part of society, which wants our population to follow all capitalist thinking, initially making changes in educational policies, since when we make changes in educational methods we are making changes in the way of thinking of society.